Struktur Kolokasi Bahasa Arab: (Suatu Kajian Fenomena Linguistik) - Yuslin Kasan (Al-Lisan: Jurnal Bahasa, 2019)
This research is about collocation in the Arabic language. Collocation in the Arabic language is called al-tadhāmma. The purpose of this study is to describe the type or category of language collocation in Arabic. This research is library research. The technique of data collection used distributional, then analyzed qualitatively. The results of this study indicate that there are two categories of language collocation found in research sources namely grammatical collocation and lexical collocation. The characteristics of grammatical collocation are usually prepositions that can be accompanied by verbs and nouns, where the prepositions used are the prepositions في (fî), إلى (ilâ), على (alâ), عنْ (an), لِ (li) and بِ (bi) and adverb تَحْت (tachta), Whereas lexical collocation is collocation formed from nouns, verbs, adjectives, which are used for certain words only.